Effects of effective microorganism to the properties of concrete containing ordinary Portland cement and blended cement - Samsiah Ahmad @ Abdul Rahman, 1991-; Abdul Rahman Mohd. Sam; Fakulti Kejuruteraan Awam (2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2014